A Sociolinguistic Analysis of Refusal Strategies in Yorùbá Culture - Jelili Adeoye (Lingual: Journal of Language and Culture, 2026)
This study examines the sociolinguistic analysis of refusal strategies among the native speakers of Yorùbá. Refusal verbal acts portend failing to engage in the actions proposed by the speaker in a discussion, which could be an assistance, advice, gift, attending ceremonies among others. These strategies have both linguistic and cultural colourations and they linger between ancient and modern societies. This simply shows refusal strategies among the Yoruba people have evolved through generations. Thus, some borrowed cultures have been directly incorporated and integrated into the refusal acts through modernisation. Contextually, refusal strategies mediate between high-context culture and low-context culture. In low-context culture politeness and courtesy are not prioritised, refusal verbal acts in this context are presented the way they occur without making recourse to the settings and status of people. Although, this is not native to the Yoruba culture, it crept into the system through western education. Thus, friendship, equal and low status could be indices that prompt direct refusal in a discourse. However, high-context culture presupposes the use of politeness with its core values. It takes settings, participant and environment of discourse into consideration and a high premium is given to respect and honour in addressing refusal from other people. The data in this study were drawn from recorded utterances of some Yorùbá language speakers and Yorùbá films. Our analysis is predicated on the Dell Hymes (1972) Ethnography of Communication. Findings in this research reveal that the Yorùbá culture permits indirect refusal more than the direct ones. As a result, refusal demands courtesy and mutual respect. It is also noted in the study that direct refusal is a product of a borrowed culture and it is demonstrated that friendship or cordiality and equal or low status can influence the use of direct refusal. The study further establishes that indirect refusal can be used to show home training, courtesy to culture and avoidance of danger. This study contributes to the existing studies on the use of politeness principle on language verbal behaviour.